2012
DOI: 10.2169/internalmedicine.51.7881
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myocardial Infarction with a Left Main Trunk Lesion and Documented Lambda-like J Waves

Abstract: We herein describe a case of a myocardial infarction, in which Lambda-like J waves were documented. The patient was referred to our hospital due to ventricular fibrillation. The twelve-lead electrocardiogram (ECG) on admission showed prominent J waves in the lateral and precordial leads. Coronary angiography revealed 99% stenosis with a delay in the left anterior descending artery, 75% stenosis in the left main trunk, and possible ischemia in the conus branch. Our report addresses the possibility that ischemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The morphology of the typical patterns (i.e., the “lambda‐like” and “triangular waveform” patterns) is varied (see Figure , Supplemental Content, which illustrates the schematic representations of the (A) lambda‐like and (B) triangular waveforms). Previous studies have shown that the above specific ECG patterns are associated with an increased risk of VF and they have been identified as predictors of a poor short‐term prognosis during acute myocardial infarction (AMI) 25–29 . The novelty of this meta‐analysis is that neither the J‐point morphology nor the J‐wave amplitude significantly increased the risk of VF in the ER patients with VSA.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The morphology of the typical patterns (i.e., the “lambda‐like” and “triangular waveform” patterns) is varied (see Figure , Supplemental Content, which illustrates the schematic representations of the (A) lambda‐like and (B) triangular waveforms). Previous studies have shown that the above specific ECG patterns are associated with an increased risk of VF and they have been identified as predictors of a poor short‐term prognosis during acute myocardial infarction (AMI) 25–29 . The novelty of this meta‐analysis is that neither the J‐point morphology nor the J‐wave amplitude significantly increased the risk of VF in the ER patients with VSA.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have shown that the above specific ECG patterns are associated with an increased risk of VF and they have been identified as predictors of a poor short‐term prognosis during acute myocardial infarction (AMI). 25 , 26 , 27 , 28 , 29 The novelty of this meta‐analysis is that neither the J‐point morphology nor the J‐wave amplitude significantly increased the risk of VF in the ER patients with VSA. Moreover, the ER pattern is independent of obstructive coronary artery disease (angiographical stenosis > 50%).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The J‐wave augmentations are caused by myocardial ischemia during coronary spasm. The presence and augmentation of J waves, especially prominent slurring J waves with the characteristic ST elevation (STE) pattern, are associated with ventricular fibrillation (VF; Sato et al, ; Yamaki et al, ; Figure ).…”
Section: Discussionmentioning
confidence: 99%